FINTECH REGULATION AND GOVERNANCE FROM THE SINGAPORE PERSPECTIVE (International Journal of Islamic Business, 2025)
Through the adoption of a balanced regulatory approach that promotes technological advancement while mitigating risks, Singapore has become a global leader in fintech innovation. The Monetary Authority of Singapore (MAS) plays a crucial role in forming the ecosystem as this paper examines Singapore's fintech regulatory framework, governance mechanisms, and risk management tactics. Singapore has shown its dedication to innovation and financial stability through important initiatives like the Payment Services Act, Fintech Regulatory Sandbox, and cross-border payment links. Along with discussing new developments in green fintech and central bank digital currencies (CBDCs), the paper also discusses issues like consumer protection, cybersecurity, and decentralized technologies. Singapore offers a model for promoting inclusive and sustainable growth in the fintech industry through global cooperation and flexible policymaking.